Paradigm Shifts and Electroacoustic Music: Some personal reflections. - Truax, Barry (Organised Sound, 2015)
The author reflects on the past decades with reference to predictions of several paradigm shifts offered in the 1990s, including a broad range of issues covering acoustics, psychoacoustics, the role of the composer, compositional models, environmental sound perception, soundscape composition, and the integration of music and context. Contemporary developments that were not predicted, such as the proliferation of compressed audio, the rapid development of sound studies, the elimination of electroacoustic music from state-funded broadcasting, and the proliferation of mobile listening and online sound databases, are also discussed.